Evaluation of HIV screening at antenatal care settings in Denpasar City - Putu Cintya Denny Yuliyatni; Wayan Pujana; Citra Indriani (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: National strategy to increase the coverage of prevention of mother to child transmission (PMTCT) program in Indonesia is integrating the service into public health centres (puskesmas). In Bali, the integration has been started since 2014. After one year of program implementation, an evaluation was conducted in order to provide input and feedback for program improvement. Methods: Secondary data analysis and indepth interview with 13 key informants in Denpasar City were conducted to assess input, process and output of the integration implementation. Results: Of the 11,719 pregnant women targeted within the program, 43% were offered to undergo HIV testing and 98% of these agreed to have HIV test with 17 were found HIV positive. Interviews with key informants found that there were adequate resources both in terms of manpower, funds and equipment. Obstacles found in the implementation include different site of ANC and HIV testing facility. The other barrier was high number of pregnant mother who conducted ANC at private obstetrician which not yet included in the program. Conclusions: Integration of PMTCT into ANC services at public health centre (PHC) is an effective way to improve the uptake of HIV screening among pregnant women. However, there is a need of effective of referral systems from private midwives and PHC satellite services. The expansion of networks into private midwives and obstetrician will be instrumental in improving performance outcomes.